Avaliação das técnicas de soldagem MIG-P CA e MIG-P CC+ aplicadas ao passe de enchimento em liga de alumínio AA5083 - Fagundes, Ramon Fernandes (2014)
For contain beneficial properties, aluminum alloys are gaining more importance in different industrial areas, becoming the subject of study in several academic fields. When related to welding these alloys have some peculiarities that may hinder the union, such as microscopic oxide layer present on the metal surface. The MIG welding process, also known as GMAW, has developed versions that can be effective for welding aluminum. Knowing this, for this paper, two versions of pulsed MIG (CC + and CA) were chosen to evaluate which best suits pass by filling bevel on AA5083 aluminum sheets with 8 and 12 mm thick respectively. Furthermore, two types of wire, ER5087 and ER5183 were evaluated. To evaluate the process and versions of the wires, the high-speed cameras and thermal were used to monitor the metal transfer and the thermal behavior respectively, and the metallographic analysis for macrographic view of the weld beads and non-destructive testing by radiography for observation of possible discontinuities. It was found that the technique of MIG-P CA showed better results ahead of another technique both welding conditions imposed. When connected to the wires, they showed similar results, with uniform cords and seamless